Characterization of the robust humoral immune response to GSK2618960, a humanized anti-IL-7 receptor monoclonal antibody, observed in healthy subjects in a Phase 1 study. - Karen Liao; Keguan Chen; Sara Brett; Andrew Gehman; Ann M Schwartz; George R Gunn; Stephen L DeWall (PLoS ONE)
Interleukin-7 (IL-7) signaling modulates T cell activity and is implicated in numerous autoimmune diseases. An anti-IL-7 receptor monoclonal antibody (GSK2618960) biotherapeutic was evaluated in healthy subjects for safety, pharmacokinetics (PK), pharmacodynamics (PD) and immunogenicity in a single-dose escalation phase I study. We found that antibodies against GSK2618960 (i.e., anti-drug antibodies or ADA) developed in 83% and 100% of GSK2618960-treated subjects in the 0.6 and 2.0 mg/kg dose cohorts, respectively. Of the ADA positive subjects, 64% (7 of 11) had detectable neutralizing activity. Further investigation revealed the presence of GSK2618960-specific memory B cells, indicating the development of immunological memory for the ADAs. Ex vivo stimulation of peripheral blood mononuclear cell (PBMC) samples demonstrated a relatively strong CD4+ T cell proliferation response to GSK2618960 as compared to the control anti-RSV antibody (which is known to have only low immunogenic potential), confirming the high immunogenic potential of GSK2618960. Furthermore, GSK2618960 was found to bind in vitro monocyte-derived dendritic cells (DCs). GSK2618960 treatment of PBMCs increased the proportion of DC cells showing an increase in expression of CD83, CD86 and CD209, which indicated enhanced DC differentiation and activation relative to the isotype control anti-β amyloid antibody. Collectively, the evidence supports that the high incidence of observed clinical immunogenicity was likely related to the receptor-mediated activity by GSK2618960.